Youth Outside Education, Employment, and Training: Policy Challenges For Indonesia From International Evidence - Binta Zulfia; Etty Soesilowati; Inayati Nuraini Dwiputri (Equivalent : Journal of Economic, Accounting and Management, 2026)
The increasing number of individuals who are not in education, employment, or training (NEET)—especially among young people—represents a segment of the population that is not optimally integrated into economic activities and skills development. This condition poses significant social and economic risks if not handled properly. This study aims to examine this phenomenon through a comparative analysis of the experiences of several countries, namely China, Australia, and the United Kingdom. The discussion focuses on the causal factors, structural challenges, and policy approaches implemented in each country. In the context of Indonesia, this analysis also highlights the “Kartu Prakerja” policy as one of the government's instruments for addressing the problems faced by youth who are not in education, employment, or training. The results of the study show that although international evidence provides essential insights, differences in demographic characteristics, labor market conditions, and institutional frameworks require Indonesia to adjust the design and implementation of policies to better align with the target group's characteristics.